Comparative expression profiling in the intestine of patients with Giardia-induced postinfectious functional gastrointestinal disorders - Martinez, Cristina; Lasitschka, Felix; Thöni, Cornelia; Wohlfarth, Carolin; Braun, Alexander; Granzow, Martin; Röth, Ralph; Dizdar, Vernesa; Rappold, Gudrun; Hausken, Trygve; Langeland, Nina; Hanevik, Kurt; et al. (Neurogastroenterology and motility, 2020)
Background A Giardia outbreak in Bergen, Norway, caused postinfectious functional gastrointestinal disorders (PI-FGIDs). Despite the devastating effects of this outbreak, it presented a unique chance to investigate the implication on the dysregulation of genetic pathways in PI-FGID. Methods We performed the first comparative expression profiling of miRNAs and their potential target genes in microdissected rectal biopsies from 20 Giardia-induced PI-FGID patients vs 18 healthy controls by nCounter analysis. Subsequently, candidates were validated on protein level by immunostaining. Key Results miRNA profiling on rectal biopsy samples from 5 diarrhea-predominant PI-IBS cases compared to 10 healthy controls revealed differential expression in the epithelial layer. The top five regulated miRNAs were implicated in GI disease, inflammatory response, and immunological disease. Subsequently, these miRNAs and 100 potential mRNA targets were examined in 20 PI-FGID cases and 18 healthy controls in both the mucosal epithelium and the lamina propria. Although deregulation of the selected miRNAs could not be verified in the larger sample set, mRNAs involved in barrier function were downregulated in the epithelium. Pro-inflammatory genes and genes implicated in epigenetic modifications were upregulated in the lamina propria. Immunostaining for selected candidates on 17 PI-FGID cases and 16 healthy controls revealed increased tryptase levels as well as a decreased and aberrant subcellular expression of occludin. Conclusions and Inferences Genes relevant to immune and barrier function as well as stress response and epigenetic modulation are differentially expressed in PI-FGIDs and may contribute to disease manifestation.
Gesehen am 16.08.2021